Feeling Touch Through Glass: A Modified Rubber Hand Paradigm. (September 2017) - White, Rebekah C.; Li, Jiexin; Shacklette, David
A variation on the rubber hand paradigm creates a striking illusion in which it seems to the participant that she or he is feeling touch through glass. This illusion provides insight about how individuals make use of predictive signals for integrating vision and touch.